Enhancing Students' Understanding of Quran and Hadith through Cooperative Learning Model at MA. Syaikh Zainuddin NW Anjani - Azwar Anas; Mahsyat (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students' understanding of Quran and Hadith at MA. Syaikh Zainuddin NW Anjani by implementing the Cooperative Learning model. The Quran and Hadith are fundamental sources of Islamic knowledge, and their study is essential in shaping students' understanding of Islamic principles and values. However, traditional teaching methods in this subject often lead to passive learning and limited student engagement. The research seeks to explore how the Cooperative Learning model, which emphasizes group collaboration and peer interaction, can enhance students' comprehension and active participation in the study of Quran and Hadith. The study was conducted in two cycles, involving 11th-grade students at MA. Syaikh Zainuddin NW Anjani. In each cycle, students worked in small groups, where they studied different sections of the Quran and Hadith. Afterward, they collaborated within their groups to share and discuss their findings, reinforcing their understanding of the material. Data were collected through observations, student surveys, and pre- and post-tests to measure improvements in student engagement and understanding. The results of the research indicated a significant improvement in both student engagement and academic achievement. The Cooperative Learning model facilitated active interaction among students, allowing them to learn from one another and deepen their understanding of complex Quranic and Hadith concepts. Moreover, students exhibited better communication and collaboration skills, which enhanced their overall learning experience. This study demonstrates that the Cooperative Learning model is an effective approach to teaching Quran and Hadith, providing a more interactive and engaging learning environment. It suggests that educators in Islamic education settings can adopt this model to foster deeper understanding and active participation among students.